2010
DOI: 10.1111/j.1553-2712.2010.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medicine Quality Improvement and Patient Safety Curriculum

Abstract: PrefaceAll of us who have worked on this curriculum are career emergency physicians (EPs) who have become leaders with a focus on emergency medicine (EM) quality and safety.About 2 years ago, I approached my colleagues of the American College of Emergency Physicians Quality Improvement and Patient Safety (ACEP QIPS) Section and dreamed an idea of creating an EM quality and safety curriculum: an outline that would explain a topic few EPs understand. That outline would be used as a curriculum to teach our EM res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…Similarly, earlier studies have shown that care professionals' work experience combined with clear instructions contribute to high quality emergency care. [13,15,25] Instructions significantly influence the success of the initial assessment and of the entire emergency care pathway. [36] They can also help in the effort to reach evidence-based, good practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, earlier studies have shown that care professionals' work experience combined with clear instructions contribute to high quality emergency care. [13,15,25] Instructions significantly influence the success of the initial assessment and of the entire emergency care pathway. [36] They can also help in the effort to reach evidence-based, good practices.…”
Section: Discussionmentioning
confidence: 99%
“…Their experiences will be valuable when seeking to detect risks and prevent human errors. [24,25] Studying care professionals' experiences of the work environment, equipment and factors that affect patient safety can also help to develop the quality of emergency care. [26] Aims The paper discusses factors that influence care quality and patient safety in out-of-hospital emergency care as experienced by emergency care professionals.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Welch, Slovis, Jensen, Chan, & Davidson, 2006 proposed a quality improvement curriculum for emergency medicine residents that is multi-faceted and encompasses many broad topics including performance metrics, operations management, information technology, and patient safety. [6] Finally, in 2010, Kelly et al [7] published an emergency medicine quality improvement and patient safety curriculum with the goal of providing education to ensure the delivery of high quality (safe, effective, efficient, equitable, timely, and patient-centered) emergency care. While these studies helped to establish directions for future curriculums, there are currently limited additional resources available to aid programs in the development of an administrative curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that systematic action is required to recognize risks and to prevent human error [26,27]. It may be added in this context that a conceptual model has been proposed [28], suggesting that the safety and quality of patient care, as well as the occupational safety of care providers, can be assessed in terms of structure, process or outcome of care.…”
Section: Introductionmentioning
confidence: 99%